Dosimetric assessment of brass mesh bolus for postmastectomy photon radiotherapy. (25th July 2016) - Manger, Ryan; Paxton, Adam; Cerviño, Laura
Abstract : Brass mesh bolus has been shown to be an acceptable substitute for tissue‐equivalent bolus to increase superficial dose for chest wall tangent photon radiotherapy. This work investigated the increase in surface dose, the change in the dose at depth, and the safety implications of higher energy photon beams when using brass mesh bolus for postmastectomy chest wall radiotherapy. A photon tangent plan was delivered to a thorax phantom, and the superficial dose ranged from 40%–72% of prescription dose with no bolus. The surface dose increased to 75%–110% of prescription dose with brass mesh bolus and 85%–109% of prescription dose with tissue‐equivalent bolus. It was also found that the dose at depth when using brass mesh bolus is comparable to that measured with no bolus for en face and oblique incidence. Monte Carlo calculations were used to assess the photoneutron production from brass mesh bolus used with 15 MV and 24 MV photon beams. The effective dose from photoneutrons was approximated and found to be relatively small, yet not negligible. Activation products generated by these photoneutrons, the surface dose rate due to the activation products, and the half‐life of the activation products were also considered in this work. The authors conclude that brass mesh bolus is a reasonable alternative to tissue‐equivalent bolus, and it may be used with high‐energy beam; but one should be aware of the potential increased effective dose to staff and patients due to the activation products produced by photoneutrons. PACS number(s): 87.53.Kn, 87.55.K